2004
DOI: 10.1074/jbc.m400791200
|View full text |Cite
|
Sign up to set email alerts
|

PimF, a Mannosyltransferase of Mycobacteria, Is Involved in the Biosynthesis of Phosphatidylinositol Mannosides and Lipoarabinomannan

Abstract: Phosphatidylinositol mannosides (PIMs) and their related molecules lipomannan (LM) and lipoarabinomannan (LAM) are important components of the mycobacterial cell wall. These molecules mediate host-pathogen interactions and exhibit immunomodulatory activities. The biosynthesis of these lipoglycans is not fully understood. In this study, we have identified a mycobacterial gene (Rv1500) that is involved in the synthesis of PIMs. We have named this gene pimF. Transposon mutagenesis of pimF of Mycobacterium marinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
70
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 39 publications
3
70
0
Order By: Relevance
“…According to the nomenclature for mannosyltransferases involved in PIM biosynthesis, we have designated this enzyme PimE. Previously, PimF was reported as a mannosyltransferase involved in the later stage of PIM/LAM biosynthesis (27). However, a recent study suggests that this enzyme is involved in the biosynthesis of glycosylated acyltrehalose lipooligosaccharides rather than PIM (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the nomenclature for mannosyltransferases involved in PIM biosynthesis, we have designated this enzyme PimE. Previously, PimF was reported as a mannosyltransferase involved in the later stage of PIM/LAM biosynthesis (27). However, a recent study suggests that this enzyme is involved in the biosynthesis of glycosylated acyltrehalose lipooligosaccharides rather than PIM (28).…”
Section: Discussionmentioning
confidence: 99%
“…PimC has been identified in M. tuberculosis as the third mannosyltransferase, but the gene is only present in some clinical strains of M. tuberculosis and absent from M. smegmatis, suggesting that there must be another gene involved in this step (26). PimF was reported as a gene involved in LM synthesis (27), but later redefined as a glycosyltransferase involved in the synthesis of lipooligosaccharide (28). The only other gene known to be involved in mycobacterial GPI biosynthesis is EmbC, which is an arabinosyltransferase involved in the synthesis of the arabinan side chain of LAM (29).…”
mentioning
confidence: 99%
“…It remains unclear whether the loss of viability of inositol-starved cells is due to loss of specific polar PIM species or the global loss of all inositol lipids. M. smegmatis and M. marinum mutants with defects in apolar PIM biosynthesis have recently been generated (30). 3 These mutants display a relatively mild growth and colony phenotype but also accumulate high levels of PIM precursors (30).…”
Section: Discussionmentioning
confidence: 99%
“…M. smegmatis and M. marinum mutants with defects in apolar PIM biosynthesis have recently been generated (30). 3 These mutants display a relatively mild growth and colony phenotype but also accumulate high levels of PIM precursors (30). Thus, whereas polar PIMs may be important for cell wall biogenesis FIG.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that this is the direct precursor of lipomannan, characterized by a linear ␣(136)-linked mannan backbone linked with ␣(132) mannopyranose side chains and that lipomannan is further glycosylated with arabinan to produce lipoarabinomannan (22). Recently, Alexander and co-workers (23) reported that, in M. marinum, a glycosyltransferase, termed "PimF, " was involved in the biosynthesis of higher molecular weight PIMs, specifically PIM 7 from PIM 5 . However, the thin layer chromatographic (TLC) behavior of the putative PIM 7 was reminiscent of a highly antigenic polar phosphorus-free glycolipid isolated previously from M. marinum (24).…”
mentioning
confidence: 99%